Thiamylal anaesthetic therapy for febrile refractory status epilepticus in children. (August 2020) - Ishida, Yusuke; Nishiyama, Masahiro; Yamaguchi, Hiroshi; Tomioka, Kazumi; Tanaka, Tsukasa; Takeda, Hiroki; Tokumoto, Shoichi; Toyoshima, Daisaku; Maruyama, Azusa; Seino, Yusuke; Aoki, Kazunori; Nozu, Kandai; et al.
Abstract: Purpose: To evaluate barbiturate anaesthetic therapy using thiamylal for febrile refractory status epilepticus (fRSE) in children. Methods: This was a review of a prospectively-collected database between April 2012–March 2016 for fRSE cases treated with thiamylal anaesthetic therapy in a single paediatric hospital in Japan. The sample comprised 23 children (median age, 23 months) with fRSE that underwent thiamylal anaesthetic therapy for convulsive seizures lasting longer than 60 min, sustained after intravenous administration of benzodiazepine and non-benzodiazepine anticonvulsants. The intervention comprised protocol-based thiamylal anaesthetic therapy with bolus administration. We measured the dose and time required to achieve the burst suppression pattern (BSP) on electroencephalography, seizure recurrence, death, neurological sequelae, and complications. Results: All patients except one reached the BSP. The thiamylal median dose until reaching the BSP was 27.5 mg/kg, and the median time from thiamylal administration to reaching the BSP was 109.5 min. There was one case of immediate treatment failure and one of withdrawal seizure, but no breakthrough seizure. No deaths occurred during treatment, and neurological sequelae occurred in four cases (17%). Vasopressors were administered in all cases. Other complications included 11 cases of pneumonia and one of enterocolitis. Conclusion: We revealed the time and dose required to reach the BSP with thiamylal anaesthetic therapy using bolus administration in children. Our results suggested that reaching the BSP with bolus administration requires markedly less time than without bolus administration, rarely causes seizure recurrence in paediatric fRSE, and causes haemodynamic dysfunction and infections as often as observed without bolus administration.